Centralized Bodies of Collective Representation in the Fragmented Company: A Power Resource? - Devetter, François-Xavier; Geymond, Maé; Perez, Coralie; Perraudin, Corinne; Thèvenot, Nadine; Valentin, Julie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
AbstractCould “centralized” bodies of collective representation constitute a power resource for employees in contemporary fragmented work organizations? Referring to the particular features of the institutional framework in France, this article links the theory of power resources to the concept of institutional toying to show that the power resources of managers allow them to make use of institutional shortcomings that limit the scope of these bodies as power resources for employees. The article draws on the REPONSE 2017 (DARES) survey, which sought to quantify “fragmented” organizations and their collective representation bodies. Six case studies of fragmented companies are also used to illustrate the diversity of institutional toying strategies employed by managers.SummaryThe traditional representation of a company has been undermined by processes of productive disintegration (outsourcing and geographical dispersion) and economic and financial concentration (subsidiaries). This movement has been accompanied by new collective rights in the form of bodies at the “centralized” level, which are intended to take into account the entire workforce. Referring to the particular features of the institutional framework in France, this article links the theory of power resources to the concept of institutional toying to show that the power resources of managers enable them to make use of institutional shortcomings that limit the scope of these bodies as power resources for employees. It draws on the REPONSE 2017 (DARES) survey to quantify “fragmented” companies and the collective representation bodies that operate within them. Six case studies of fragmented companies are used to illustrate the diversity of institutional toying strategies employed by managers in setting up centralized bodies. We begin by highlighting the prevalence of three forms of fragmentation (outsourcing, group, multi-site) and the limited role played within them by centralized bodies. The institutional limits of centralized bodies are then analyzed based on the power resources available to management and the diversity of strategies implemented to configure these bodies. Next, the fragmentation of companies is analyzed as an instrument for weakening employees’ power resources, as it reduces their interest and ability to participate in social dialogue, and divides and creates competition within a fragmented workforce. Finally, associational resources to overcome the divisions created by fragmentation and institutional resources to rebalance the ability to set the framework for employee consultation are discussed as solutions to restrict management leeway.